Penguatan Peran Perpustakaan Dalam Komunikasi Ilmiah (Scholarly Communication) Di Lingkungan Akademik - Irman Siswadi (Jurnal Pustakawan Indonesia, 2013)
Scholarly communication and academic environment are interelated and interdependent to each other. Academic environment is where scholars consisting of faculty members, researchers and student meet. They produce most of scholarly writing and access to scholay resources as their references. They are both author and reader components.  In library perspective, they are users. Libraries in academic environment will function well in the support of information technology. Information technology supports scholarly communication as well.  Internet, if you like, has provided  a significant support on scholarly communication process. Access to scientific writings in any formats is easier and faster using internet than other tools. Searching current articles and sending email to authors can be done directly in second.   It is clear that the use of  information technology is a must  in supporting scholarly communication. Library as an established institution that has long supported scholarly communication needs continues reformation. Sustainable action  of reform to scholarly communications have to be done.  There are many factors to be paid attention to such as university policies;  partnership between library and working units in university; involvement of civitas academica;  use of handbook; information library sites; human resources development.Keywords: Scholarly Communication,  Academic Environment, Information Technology, Library